Pharmacodynamic studies on Pycnamine - Lim, Pilar Rizalina Trinidad 1936-
Investigations of the pharmacodynamic actions, as well as acute and chronic toxicity studies of pycnamine were done. The alkaloid was found to cause hypotension of brief duration accompanied in most instances by bradycardia, tachypnea, and increase in tidal air and minute volume. The above response to pycnamine seemed to be an interplay of several factors, namely, direct pheripheral vasodilatation, ganglionic blocking action, central and thru reflex mechanisms. There was a greater degree of hypotension from intraarterial and intracardiac injections as compared to the intravenous injection of the alkaloid. This offered two possibilities: (1) the presence of receptors in the femoral arteries and (2) possible filtration in the lungs. It caused neuromuscular stimulation or neuromuscular block which may or may not be preceded by an initial neuromuscular stimulation depending on the dose and the susceptibility of the particular dog. The neuromuscular stimulation was antagonized by d-tubocurarine, but the complete paralysis was not antagonized by neostigmine. LD50 of intravenous pycnamine in albino rats was found out to be 33.5 mg./kg.. Gangrene was formed at the site of injection after a few days of daily intravenous injections. Gross and histopathological findings with albino rats given daily intraperitoneal injections of 20 mg./kg. for one month revealed bloated abdomen, generalized peritonitis, and abscess formation in the lungs.